Problems in Teaching English in Indian Classrooms: Issues and Remedies - Sarita Jain (Yayasan Karinosseff Muda Indonesia, 2020)
This paper examines the present status of English as a second language in India. It defines language and identifies the factors that affect second language learning. It discusses different problems faced by learners of English and what is the right way of language acquisition for second language learners in India. Language acts as an instrument to express effectively in various communicative situations. However, it is the very second language which requires a conscious and diligent, systematic efforts to acquire or master it. Second language acquisition is really a big challenge for all native speakers of that language who really deal with it. The majority of Indian students, particularly from rural pockets, especially in the states of Bihar, eastern U.P. and Maharashtra, consider this seven –letter word as a magical and mystical word. A feeling of uneasiness sets in, the moment they hear something in English. As a result of this, teachers who handle English classes face insurmountable difficulties. Students find it difficult to listen and to understand the English language. What are the reasons for this? What are the remedial measures to be taken to alleviate these problems? This paper is an attempt to discuss the nature of second language acquisition and the factors responsible for its slow acquisition. Appropriate and adequate remedial measures are cited for the successful rectification of these problems.